Formulation and Evaluation of Transdermal Patches of Donepezil - R. Madan, Jyotsana; S. Argade, Nitin; Dua, Kamal (Recent Patents on Drug Delivery & Formulation, 2015)
Aims and Background: Donepezil (DNZ) is a centrally acting reversible acetyl cholinesterase inhibitor. The main therapeutic use of donepezil is in the treatment of Alzheimer’s disease. The present research work pertains to the preparation of transdermal patches of donepezil with the objective to improve its patient compliance, therapeutic efficacy and to reduce the frequency of dosing and side effects as well as to avoid its extensive first pass metabolism. The recent patents on Rivastigmine (WO2013150542A2), Xanomeline (US5980933A) and Propentofylline (CA2255580A1) helped in selecting the drug and polymers. Materials and Methods: The transdermal patches were prepared using various polymers in combination with the plasticizer and penetration enhancers. The physicochemical parameters like folding endurance, thickness, drug content, content uniformity, moisture absorption, weight variation, and drug permeation studies of the optimized patches were studied. Results: The system containing Eudragit S -100, Eudragit E -100 and HPMC as matrix forming agent and glycerine as plasticizer was the best formulation. The in vitro release data was treated with kinetic equations and it followed zero order release. The diffusion study was carried out using rat skin showed 89% drug was released within 72 hours. Tween-80 (0.83 % w/w) was found to be the best among all penetration enhancers. All the transdermal patches had the desired physical properties like tensile strength, folding endurance, flatness and water vapor transmission rate etc. Conclusion: The study concluded that that transdermal patch can extend the release of donepezil for many hours and also ensure enhanced bioavailability, further it also helps in avoiding the first pass effect.
Keywords: Donepezil